2009
DOI: 10.1021/ja907918r
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the Integral Membrane Protein VDAC-1 in Lipid Bilayer Nanodiscs

Abstract: Biophysical studies of membrane proteins are often impeded by the requirement for a membrane mimicking environment. Detergent micelles are the most common choice, but the denaturing properties make them unsatisfactory for studies of many membrane proteins and their interactions. In the present work, we explore phospholipid bilayer nanodiscs as membrane mimics and employ electron microscopy and solution NMR spectroscopy to characterize the structure and function of the human voltage dependent anion channel (VDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 36 publications
2
134
2
3
Order By: Relevance
“…Application of solution NMR methods to study the structure of membrane proteins reconstituted into phosphoplipid vesicles is hindered by the very large size of the vesicles, which effectively ranges from tens of megadaltons to gigadaltons depending on their radii and leads to broadening beyond detection of resonances from structured parts of the proteins. This problem can be alleviated by incorporation of membrane proteins into nanodiscs (30)(31)(32), which leads to effective molecular weights in the 150-400 kDa range but still requires protein perdeuteration to obtain high-quality NMR data for structured regions. In the current study, we made no attempt to observe resonances from structured regions of reconstituted synaptobrevin and focused on determining which regions of its sequence remain flexible upon anchoring to a phospholipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of solution NMR methods to study the structure of membrane proteins reconstituted into phosphoplipid vesicles is hindered by the very large size of the vesicles, which effectively ranges from tens of megadaltons to gigadaltons depending on their radii and leads to broadening beyond detection of resonances from structured parts of the proteins. This problem can be alleviated by incorporation of membrane proteins into nanodiscs (30)(31)(32), which leads to effective molecular weights in the 150-400 kDa range but still requires protein perdeuteration to obtain high-quality NMR data for structured regions. In the current study, we made no attempt to observe resonances from structured regions of reconstituted synaptobrevin and focused on determining which regions of its sequence remain flexible upon anchoring to a phospholipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, our data show that synaptobrevin behaves very similarly on nanodiscs and on phospholipid vesicles, confirming the notion that nanodiscs provide a faithful membrane model. Although our NMR experiments of synaptobrevin in nanodiscs focused on analyzing flexible regions, recent studies have shown that good-quality NMR data can also be obtained for structured regions of membrane proteins inserted into nanodiscs (30)(31)(32). Hence, the nanodisc approach provides a promising avenue for structural studies of membrane proteins in their actual bilayer environment.…”
Section: Soluble Synaptobrevin Snare Motif Binds To Dpc Micelles But mentioning
confidence: 99%
“…Because the N-terminal segment of VDAC is involved in voltage gating, it may adopt different conformations depending on the factors external to the protein (Ujwal et al, 2008). Using electron microscopy and NMR studies with a nanodisc technology, it has been demonstrated that the presence of phospholipid membrane facilitates this targeting to or interaction with different proteins (Raschle et al, 2009). Because VDAC1 knockout mice are viable (Anflous et al, 2001), it is likely that additional mechanisms promote cholesterol transport, possibly through the interaction of the -1 receptor associated with VDAC2 at the MAM region.…”
Section: Discussionmentioning
confidence: 99%
“…A number of membrane proteins, including cytochrome P450 monooxygenase [35,44], bacteriorhodopsin [45], rhodopsin [46,47], β2-adrenergic receptor [48,49], and the human mitochondrial voltage-dependent anion channel (VDAC1) have been studied using nanodisc technology [50].…”
Section: Artificial Discs a Nanodiscsmentioning
confidence: 99%